A world on the wing : the global odyssey of migratory birds - Weidensaul, Scott (UK: Picador, 2021)
"An exhilarating exploration of the science and wonder of global bird migration. In the past two decades, our understanding of bird migration-the navigational and physiological feats that enable birds to cross immense oceans or fly above the highest mountains, to go weeks without sleep, or remain in unbroken flight for months at a stretch-has exploded. Scientists have made astounding discoveries: certain species, such as thrushes, can avoid dehydration over long flights by "drinking" from their own muscles and organs, extending their flight range by almost thirty percent, or more than two thousand miles, and while we've known for decades that birds are somehow able to orient themselves using earth's magnetic field, a new leading theory is that they do so through a form of quantum entanglement. In A World on the Wing, author and researcher Scott Weidensaul shares these and other revelations to convey both the wonder of bird migration and its global sweep, taking the reader from the shores and mudflats of the Yellow Sea in China, to the remote mountains of northeastern India, and to the salt lakes in southern Cyprus in the Mediterranean. Weidensaul also introduces those trying to preserve global migratory patterns in the face of climate change and other rising challenges"--
Includes bibliographical references and index.
Keywords: Birds -- Migration; Migratory birds; Flyways